144k views
1 vote
If p (x) = 3x^3+2x^2+4x^4+3 and q (x) = 3x^4-2-x+5^2 .find p (x) - q (x)​

User Aryaxt
by
6.4k points

1 Answer

5 votes

Answer:

4x⁴-3x⁴+5x³-3x²+1

Explanation:

Given that p (x) = 3x^3+2x^2+4x^4+3 and q (x) = 3x^4-2-x+5x^2

p (x) - q (x)​ = 3x^3+2x^2+4x^4+3 - (3x^4-2-x+5x^2)

p (x) - q (x)​ = 3x^3+2x^2+4x^4+3 - 3x^4 + 2 + x - 5x^2

Collect the like terms

p (x) - q (x)​ = 4x⁴-3x⁴+3x³+2x²-5x²+x+3-2

p (x) - q (x)​ = 4x⁴-3x⁴+5x³-3x²+1

This givess the difference

User Dewi Jones
by
5.5k points